Inclution of Combination Double Step Down Feed And Citric Acid to Increased Efficiency in Broiler Livestock - Saputra, Wirawan Yudha; Suthama, Nyoman; Mahfudz, Luthfi Djauhari (Universitas Hasanuddin, 2014)
The aims of research is to assess and evaluate the application of a combination double step-down ( DSD ) diet and citric acid ( CA ) in improving the efficiency of broiler business . Research arranged in a completely randomized design ( CRD ) . A total of 168 broilers strains MB 202, 7 days old with average body weight of 186.23 ± 0.68 g were divided into 7 treatments and 4 replication ( @ 6 broiler ). Treatments were : T0 ( control diet without a step-down and the CA) , T1 ( DSD diet without the CA ) , T2 ( DSD diet + 0.8 % CA of lime) , T3 ( DSD diet + 0.4 % CA synthetic ) , T4 ( DSD diet + 0.8 % of CA synthetic ) , T5 ( DSD diet + 1.2 % of CA synthetic ) and T6 ( DSD diet + 1.6 % of CA synthetic ) . The parameters measured in the present research were carcass weight , feed costs and income over feed cost ( IOFC ). ). The data were subjected to analysis of variance by F test followed Duncan test ( P < 0.05 ) and orthogonal polynomials ( PO ) to determine the optimal level of the CA. The results showed that the carcass weight did not differ ( P > 0.05 ) due to treatment . The treatment combination of DSD and the CA synthetic diet from 0.4% to 1.2 % ( T3 - T5 ) significantly ( P < 0.05 ) reduced diet costs and increase IOFC compared to control ( T0 ) . Based on the calculation of PO , the CA determined the optimal level of 0.96 % . Research conclusion that the application of a combination of double step-down diet and 0.8-1.2 % citric acid can be used as an alternative to increased efficiency in broiler production .